(untitled) (Revista de Biología Marina y Oceanografía, 2020)
The Chilean jack mackerel Trachurus murphyi support an important fishery in the South-eastern Pacific Ocean and has declined considerably over time. T. murphyi have asynchronous ovarian development with an oceanic spawning (September to January). Despite the economic importance of this resource critical issue such as characteristics and dynamics of atresia, which affect the reproductive output, are unknown. Females of T. murphyi caught in different spawning seasons were analysed to describe patterns of prevalence and intensity of atresia. General linear models (GLM) were performed by using prevalence and intensity atresia as response variables and gonadosomatic index, condition factor, sea surface temperature, postovulatory follicles and month/year as explanatory variables. The batch fecundity and relative fecundity were compared between females showing atresia, postovulatory follicles and non-atretic females. The stages of atresia identified were alpha, beta and gamma. The GLM showed that variations in the prevalence and intensity of atresia were explained for all variables, except condition factor for prevalence, and gonadosomatic index for intensity of atresia. According to our results, the dynamic of alpha and beta atresia could be considered a potential proxy for any disruption of spawning season. The batch fecundity and relative fecundity were lowest compared with other Trachurus spp. This is the first assessment comparing fecundity between atretic and not atretic females for this species.